2019
DOI: 10.3390/foods8050147
|View full text |Cite
|
Sign up to set email alerts
|

Fluidized Bed Drying of Pumpkin (Cucurbita sp.) Seeds

Abstract: Pumpkin seeds are a major agricultural waste from the fresh-cut produce industry. The objective of this study was to investigate the drying behavior of untreated, whole pumpkin seeds in a fluidized bed dryer at 50–80 °C (2.87 m/s), with a view to producing a high-quality pumpkin powder from dried seeds. Seeds were dried at 50–80 °C to an average equilibrium moisture value of 0.035 to 0.006 g H2O/g DM (3.4 to 0.6% wb). Drying occurred in the falling rate period only and drying rate constants ranged from 0.0226 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 13 publications
2
16
0
3
Order By: Relevance
“…Fluidized bed granulation is often a method of choice for drying heat-sensitive compounds, including microbial cultures. Advantages, such as good temperature control, equal temperature distribution, high drying capacity, short drying time, low maintenance costs, and large-scale production, are noticeable [15][16][17][18]. To minimize the damage caused by drying and to achieve increased bacterial viability in storage time, fluidized bed immobilization of LAB is mainly performed in the presence of protective carbohydrates [15].…”
Section: Introductionmentioning
confidence: 99%
“…Fluidized bed granulation is often a method of choice for drying heat-sensitive compounds, including microbial cultures. Advantages, such as good temperature control, equal temperature distribution, high drying capacity, short drying time, low maintenance costs, and large-scale production, are noticeable [15][16][17][18]. To minimize the damage caused by drying and to achieve increased bacterial viability in storage time, fluidized bed immobilization of LAB is mainly performed in the presence of protective carbohydrates [15].…”
Section: Introductionmentioning
confidence: 99%
“…In most of the drying experiments, empirical models validate the exceptional fitting of data but overlook the basics of the drying processes. While theoretical models justify diffusion mechanism or heat and mass transfer mechanism [15], there are several investigations on mathematical modeling of pumpkin seeds drying kinetics for natural and forced convection solar dryer [6], solar tunnel dryer [16], tray drying [17], fluidized bed drying [17][18][19][20], and infrared dryer [21]. However, no study was found for pumpkin seed drying using a vibro-fluidized bed dryer.…”
Section: Introductionmentioning
confidence: 99%
“…In [3], the drying process in the moving layer is considered, where the suspended state of the seed material is ensured by blowing the drying agent at speeds of 2.39-2.87 m/s. This method does not guarantee uniform heating of the seed and causes additional energy consumption to provide the required speed of the drying agent.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%